Ethnomedical Health Care Practices among the Satar tribe of Nepal: Linking to Development Agenda - Adhikari, Lal Mani (Journal of Advanced Academic Research, 2017)
Introduction: Ethno medical Health Care Practices (EMHCP) so called traditional medicine or indigenous developing affordability of health care have increased, between as well as within populations the world over. Access to appropriate healthcare is increasingly being acknowledged as a health countries. care practices Inequities are in widely availability, adopted accessibility, phenomenon acceptability especially and in human right through international instruments such as the United Nations Human Rights Commission, Millennium Development Goals (MDGs) and the WHO. In the recent past there has been increasing interests in integration of EMHCP relevance to public health globally. In this context, there is a critical need to mainstream EMHCP into public health care to achieve the objective of improved access to healthcare facilities. Method: The study based on Primary data, conducted in Satar community which is sixth-most predominant ethnic group by population in Jhapa district of Nepal. Using Semi-structured tool as the data collection; cross sectional descriptive study was employed. The male household heads of Satar aged 24-49 years are selected as primary respondents. Fifty sampling units from 5 VDCs were selected using purposive sampling technique. The data are analyzed through Frequency and descriptive statistics to describe the preference of medication practices in common illnesses over 4 "A"s of health seeking behavior, attitude and satisfaction towards EMHCP comparing with modern medication. Result and Discussion : Overall two-third (64%) of Satar population adopts the EMHCP as majority of population has been cured through Traditional medication (50%) followed by Faith healers (32.1%) for the most common illnesses. The Illiterate category seek EMHCP more frequently with compared to the Literate Category which was found strongly significant (P<0.01). There is no significant difference between Poor and Rich category (p>0.8). However, the overall frequency of EMHCP users in both category found quite high (68%) with comparison to Modern medication. The analysis of 4 "As" model in health seeking practices, EMHCP users can afford the EMHCP compared to Modern medication users for seeking Modern medication which was found very significant (P<0.001). The availability, accessibility and Acceptability frequency for EMHCP is very high compared to the Modern medicine providing the composite score 0.938 vs. 0.740 respectively. The mean attitudinal scale of EMHCP over the modern medicine found to be 4.12 out of 5 which is very significant. Conclusion: EMHCP phenomenon is widely prevalent in the disadvantaged and marginalized ethnic societies. People adopted different types of EMHCP according to their available choices in the common public health problems for their various health needs. Journal of Advanced Academic Research Vol. 3, No. 2, 2016, Page: 55-65